Key Insights From the Development and Implementation of a Novel Virtual Interview Process for Medical School Admissions During the COVID-19 Pandemic. (4th May 2021) - Garden, Evan; Loebel, Emma; Sanky, Charles; Chudow, Jacquelyn; Fallar, Robert; Parkas, Valerie
Abstract : Supplemental Digital Content is available in the text. Abstract : Problem: During the COVID-19 pandemic, medical schools have offered a virtual application process. Minimal literature is available to guide best practices. Approach: The Icahn School of Medicine at Mount Sinai (ISMMS) implemented a completely virtual interview (VI) process in April/May 2020. Large-group sessions for applicants, interviews with applicants, and ISMMS Admissions Committee meetings occurred via Zoom (Zoom Video Communications, Inc., San Jose, California). Large-group sessions and committee meetings occurred via communal conference calls, while one-on-one, semistructured interviews occurred in individual breakout rooms. ISMMS offered live, virtual question-and-answer sessions with students and faculty, plus digital resources describing program features. After the interview day, applicants and interviewers were invited to complete anonymous surveys regarding their experiences with and perspectives of VI. Outcomes: Of 125 applicants and 20 interviewers, 99 (79%) and 18 (90%), respectively, completed at least part of the survey. Of the applicants, 85/95 (89%) agreed VI met or exceeded expectations, with many praising the day's organization and convenience, and 71/95 (75%) agreed they received a sufficient sense of the student body. A minority (n = 39/95 [41%]) felt limited in their ability to learn about the institution (commonly related to their inability to tour campus), and a majority (n =74/91 [81%]) would have preferred an in-person interview. Most interviewers felt comfortable assessing applicants' verbal communication skills (n = 13/16 [81%]), and most (n = 12/17 [71%]) felt VI should be an option for future applicants. Next Steps: VI, likely to be a temporary-but-universal fixture of upcoming application cycles, may benefit applicants and interviewers alike by saving resources and diversifying those involved. Next steps are developing programming that will permit applicants to virtually explore the institution and connect more with current students. Future research should evaluate potential bias in VI to ensure an equitable application process for all.